Anti-icing wave-absorbing multifunctional composite material structure and preparation method thereof
Patent Information
- Application Number
- CN202611424575.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]本发明针对现有防冰涂层耐久性不足、主动除冰依赖光照条件、吸波功能与防冰功能难以有效集成等问题,提供一种防除冰吸波多功能复合材料结构及其制备方法
1.本发明采用具有内空腔和壳间空腔的双空腔磁性吸波填料,配合石墨化碳层的阻抗渐变设计,有助于使涂层获得优异吸波能力。双空腔结构在电磁波传播路径上引入大量空气-固体界面,增强了界面极化损耗;石墨化碳层中内层高石墨化区域提供传导损耗,外层低石墨化区域有利于电磁波从空气进入涂层内部,减少表面反射,从而解决了单一损耗机制吸波材料频带窄、匹配厚度大的问题。
Smart Images

Figure FT_1 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional coating technology, and in particular to a multifunctional composite material structure for anti-icing, de-icing, and wave-absorbing purposes, and its preparation method. Background Technology
[0002] Outdoor equipment in fields such as wind power generation, air transport, and power transmission is highly susceptible to surface icing in low-temperature and high-humidity environments, leading to decreased equipment performance, reduced operating efficiency, and even safety issues. Traditional thermal and mechanical de-icing methods are energy-intensive, require complex equipment, and are ill-suited to harsh environments. In recent years, superhydrophobic coatings have gained attention due to their passive anti-icing advantages; however, they suffer from insufficient mechanical stability, their surface microstructure is easily damaged by wear, and the bonding force between the polymer matrix and fillers is weak, resulting in a rapid decline in coating performance over long-term use.
[0003] To address the durability issue of passive anti-icing coatings, researchers have attempted to incorporate materials with photothermal conversion capabilities into the coatings, developing coatings capable of active de-icing by utilizing the heat generated by sunlight. However, the de-icing effect of these coatings is heavily dependent on ambient light conditions, and they are ineffective on cloudy days, at night, or in low-light environments.
[0004] In addition, absorbing materials with special internal cavity structures have attracted attention because they can improve the absorption performance. Their internal cavity structure is conducive to multiple reflections and loss of electromagnetic waves, and is considered an effective structural design to improve the absorption effect.
[0005] Regarding coating substrate materials, while some existing hybrid coating systems possess good durability and weather resistance, they typically lack anti-icing capabilities. Other resin materials, although exhibiting good adhesion, are insufficient to simultaneously achieve multiple functions such as anti-icing, de-icing, and wave absorption in a single material system. Therefore, integrating long-lasting anti-icing, de-icing, and wave absorption functions into a single coating system remains a pressing technical challenge in this field. Summary of the Invention
[0006] This invention addresses the problems of insufficient durability of existing anti-icing coatings, reliance on light conditions for active de-icing, and difficulty in effectively integrating microwave absorption and anti-icing functions. It provides a multifunctional composite material structure for anti-icing, de-icing, and microwave absorption, along with its preparation method. This structure involves synergistically introducing a magnetic microwave-absorbing filler with a double-cavity graphitized core-shell structure and a polysiloxane bridging agent into an epoxy-modified polysiloxane / organopolysilazane hybrid coating system.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: A multifunctional composite material structure for anti-icing, de-icing, and microwave absorption includes a substrate and a surface anti-icing coating disposed on the surface of the substrate. The surface anti-icing coating is formed by curing an anti-icing paint. The anti-icing paint contains the following components: epoxy-modified polysiloxane resin, organopolysilazane, dual-cavity magnetic microwave absorbing filler, polysiloxane bridging agent, curing agent, crosslinking accelerator, hydrophobic modification agent, leveling agent, defoamer, and mixed solvent.
[0008] The dual-cavity magnetic absorbing filler is a multi-layer core-shell structure formed by template pyrolysis to create an inner cavity and selective etching between the carbon layer and the mesoporous silica shell to create an inter-shell cavity. The carbon layer contains iron oxide nanoparticles, and the surface of the mesoporous silica shell is grafted with amino functional groups.
[0009] The polysiloxane bridging agent has a polymethylhydrosiloxane backbone, on which three side groups—epoxypropyl, perfluorodecyl, and phosphate ester—are grafted, and active silane-hydrogen bonds are retained.
[0010] Preferably, by weight, the anti-icing coating comprises 40-70 parts of epoxy-modified polysiloxane resin, 10-30 parts of organopolysilazane, 5-25 parts of double-cavity magnetic microwave absorbing filler, 3-8 parts of polysiloxane bridging agent, 5-15 parts of curing agent, 0.5-3 parts of crosslinking accelerator, 1-5 parts of hydrophobic modifying agent, 0.2-1.0 parts of leveling agent, 0.2-1.0 parts of defoamer, and 50-150 parts of mixed solvent.
[0011] Preferably, the dual-cavity magnetic absorbing filler is prepared by a method comprising the following steps: A1. Add deionized water, melamine, and 37wt% formaldehyde aqueous solution to a reaction vessel. After stirring and dissolving, adjust the pH to 4.0-5.5 with formic acid, heat to 60-80℃ and react for 2-6 hours. After centrifugation, washing and drying, obtain melamine-formaldehyde microsphere templates. The weight ratio of melamine, 37wt% formaldehyde aqueous solution and deionized water is 5-15:10-30:100.
[0012] A2. The melamine-formaldehyde microsphere template obtained in A1 was dispersed in a mixed solvent of anhydrous ethanol and deionized water. Resorcinol, 37wt% formaldehyde aqueous solution, and nano-iron oxide with a particle size of 20-50 nm were added sequentially. After ultrasonic dispersion, the pH was adjusted to 9-11 with ammonia water, and the temperature was raised to 60-80℃ for 4-12 hours. After centrifugation, washing, and drying, core-shell microspheres were obtained. The weight ratio of melamine-formaldehyde microsphere template, resorcinol, 37wt% formaldehyde aqueous solution, nano-iron oxide, anhydrous ethanol, and deionized water was 5-15:10-30:15-45:5-20:100:50-100.
[0013] A3. The core-shell microspheres obtained in A2 were dispersed in a mixed solution of anhydrous ethanol and deionized water containing hexadecyltrimethylammonium bromide. The pH was adjusted to 9-11 with ammonia. The temperature was raised to 40-60℃ and tetraethyl orthosilicate was added dropwise. The reaction was maintained at this temperature for 6-12 hours. After centrifugation, washing, and drying, three-layer core-shell microspheres were obtained. The weight ratio of core-shell microspheres, tetraethyl orthosilicate, hexadecyltrimethylammonium bromide, anhydrous ethanol, and deionized water was 5-20:10-30:5-15:100:50-100.
[0014] A4. The three-layered core-shell microspheres obtained in A3 are placed in a tube furnace and heated to 700-900℃ under argon protection at a rate of 2-5℃ / min. The temperature is then maintained at this temperature for 2-6 hours, and the carbonized product is obtained by natural cooling.
[0015] A5. Disperse the carbonized product obtained in A4 in deionized water, add sodium hydroxide and stir and etch at 60-80℃ for 2-6 hours. After centrifugation, washing and drying, a double-cavity core-shell structure packing is obtained, wherein the weight ratio of carbonized product, sodium hydroxide and deionized water is 100:5-20:200-500.
[0016] A6. The double-cavity core-shell structure packing obtained in A5 is dispersed in anhydrous ethanol, deionized water and 3-aminopropyltriethoxysilane are added, the pH is adjusted to 8-10 with ammonia, and the reaction is carried out at 50-70℃ for 6-12 hours. After centrifugation, washing and drying, the double-cavity magnetic absorbing packing is obtained, wherein the weight ratio of the double-cavity core-shell structure packing, 3-aminopropyltriethoxysilane, anhydrous ethanol and deionized water is 100:2-8:300-500:5-15.
[0017] Preferably, the polysiloxane bridging agent is prepared by a method comprising the following steps: S1. Add polymethylhydrosiloxane and toluene to a reaction vessel equipped with a stirrer and a nitrogen purging device, purge with nitrogen and heat to 80-90°C, add Karstedt catalyst, the amount of Karstedt catalyst being 0.05%-0.2% of the mass of polymethylhydrosiloxane, add allyl glycidyl ether dropwise, the amount of allyl glycidyl ether being 4%-12% of the total molar number of active silane-hydrogen bonds in the polymethylhydrosiloxane, the dropwise addition time being 1-2 hours, and keep the reaction at the temperature for 4-8 hours to obtain an epoxy-modified hydrogen-containing polysiloxane solution.
[0018] S2. Cool the S1 epoxy-modified hydrogen-containing polysiloxane solution to 70-80°C, add Karstedt catalyst, the amount of Karstedt catalyst added being 0.02%-0.1% of the mass of the polymethylhydrosiloxane, add 1H,1H,2H,2H-perfluorodecyl acrylate dropwise, the amount of 1H,1H,2H,2H-perfluorodecyl acrylate being 0.5%-3.0% of the total molar number of initial active Silane-hydrogen bonds in the polymethylhydrosiloxane, the dropwise addition time is 1-2 hours, and the reaction is maintained at the temperature for 3-6 hours to obtain an epoxy / fluoroalkyl co-modified hydrogen-containing polysiloxane solution.
[0019] S3. Cool the S2 epoxy / fluoroalkyl co-modified hydrogen-containing polysiloxane solution to 55-65°C, add Karstedt catalyst (0.02%-0.08% of the mass of the polymethylhydrosiloxane), and add vinyl dimethyl phosphate (0.5%-5.0% of the total molar number of initial active Silane-hydrogen bonds in the polymethylhydrosiloxane). Control the temperature during the addition process to not exceed 70°C, and the addition time to be 30-60 minutes. Maintain the reaction temperature for 2-4 hours. After washing with ethanol, allow the mixture to stand and separate into layers, separate the lower organic phase, and remove the solvent under vacuum to obtain the polysiloxane bridging agent.
[0020] Preferably, the particle size of the melamine-formaldehyde microsphere template in A1 is 0.5–5.0 μm.
[0021] Preferably, the sodium hydroxide etching temperature in A5 is 60-80°C, and the etching time is 2-6 hours.
[0022] Preferably, the polymethylhydrosiloxane in S1 has a hydrogen content ≥1.58% and a viscosity of 15-40 mm at 25°C. 2 / s; the amount of toluene used is 1 to 3 times the mass of polymethylhydrosiloxane.
[0023] Preferably, the temperature for vacuum solvent removal in S3 is 80–100°C, and the vacuum degree is -0.095–-0.098 MPa.
[0024] Preferably, the curing agent is an amine curing agent or an anhydride curing agent, the crosslinking accelerator is triethylenediamine, the hydrophobic modifying agent is heptadecafluorodecyltrimethoxysilane, the leveling agent is polyether-modified polysiloxane, the defoamer is a polysiloxane defoamer, the mixed solvent is a mixture of xylene, butyl acetate and propylene glycol methyl ether acetate, with a weight ratio of 5-7:2-4:1-3, and the thickness of the surface anti-icing coating is 40-80 μm.
[0025] A method for preparing a multifunctional composite material structure for ice removal and wave absorption includes the following steps: The first step is substrate surface treatment: the substrate surface is sanded, cleaned and dried.
[0026] The second step is coating preparation: Epoxy modified polysiloxane resin, organopolysilazane, double-cavity magnetic microwave absorbing filler, polysiloxane bridging agent, hydrophobic modification agent and mixed solvent are mixed and dispersed at high speed at 1000-3000 rpm for 20-40 minutes until uniform. Then, curing agent, crosslinking accelerator, leveling agent and defoamer are added and stirred until uniform to obtain anti-icing coating.
[0027] The third step is coating and curing: the anti-icing coating is applied to the surface of the treated substrate, pre-cured at room temperature for 24 to 48 hours, and then post-cured by heating at 80 to 100°C for 2 to 4 hours to obtain the surface anti-icing coating.
[0028] The core technical principle of this invention can be understood from the following three levels: 1. Structure and electromagnetic loss mechanism of the packing layer The dual-cavity magnetic microwave absorbing filler is prepared using melamine-formaldehyde microspheres as a template through layer-by-layer coating and high-temperature carbonization. During carbonization, the template pyrolysis forms an inner cavity within the particles; subsequently, selective etching of part of the mesoporous silica shell with sodium hydroxide creates an intershell cavity between the carbon layer and the remaining silica shell, thus constructing a lightweight core-shell structure with both inner and intershell cavity characteristics. Simultaneously, the iron oxide nanoparticles play an in-situ catalytic graphitization role during carbonization, resulting in a higher degree of graphitization and stronger conductivity in the carbon layer near the catalyst source, and a relatively lower degree of graphitization and moderate dielectric constant in the carbon layer farther from the catalyst source. This gradual change in conductivity helps improve the impedance matching between the filler and free space, reducing surface reflection of electromagnetic waves. Furthermore, the outermost layer of the filler is a mesoporous silica shell modified with amino groups, serving both as a microwave absorbing functional group and providing abundant chemical anchoring sites for the phosphate groups of the polysiloxane bridging agent through the mesoporous structure and amino functional groups.
[0029] 2. Molecular design and interfacial bridging at the adjuvant level The polysiloxane bridging agent uses polymethylhydrosiloxane as the main chain and grafts three side groups—epoxypropyl, perfluorodecyl, and phosphate ester—sequentially through a stepwise hydrosilylation reaction, while retaining some active silane-hydrogen bonds. The epoxypropyl side group has a structure similar to that of epoxy-modified polysiloxane resin, improving the compatibility of the agent in the resin matrix and participating in the curing and crosslinking of the epoxy system. The retained active silane-hydrogen bonds can undergo crosslinking reactions with the active groups in organopolysilazane, enhancing the crosslinking density of the polymer network. The perfluorodecyl side group has low surface energy characteristics, migrating to the surface during coating curing to form a hydrophobic interface and reduce ice adhesion. The phosphate ester side group contains phosphoryl oxygen atoms with strong coordination ability, which can bind to the active sites on the filler surface through chemical adsorption or coordination, improving the dispersion stability of the filler in the matrix.
[0030] 3. Overall synergistic mechanism of the coating system During the coating formation process, the polysiloxane bridging agent acts as a "molecular bridge." Its phosphate ester groups anchor the surface of the inorganic filler, while the epoxy groups and active silane bonds crosslink with the epoxy resin and polysilazane, respectively. This integrates the dual-cavity magnetic microwave absorbing filler into the organic-inorganic hybrid resin network through covalent bonds, forming an integrated "filler-additive-resin" bonded structure, effectively reducing the risk of thermal mismatch at the inorganic-organic interface. In this integrated network, the dual-cavity magnetic microwave absorbing filler acts as an electromagnetic wave loss medium. The thermal effect generated by its carbon layer and magnetic components when absorbing electromagnetic waves helps melt the ice layer. Simultaneously, the composite structure of iron oxide and graphitized carbon layer serves as a photothermal conversion medium, enabling the coating to convert absorbed light energy into heat energy under illumination, thus raising the coating surface temperature and achieving active de-icing. The hydrophobic layer formed on the surface by the perfluorodecyl side groups in the polysiloxane bridging agent inhibits water droplet spreading and freezing, providing passive anti-icing functionality. Ultimately, the coating forms a robust chemical bond network at the microscopic level, achieving a unified integration of wave absorption stealth and anti-icing functions at the macroscopic level.
[0031] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention employs a dual-cavity magnetic absorbing filler with an inner cavity and an inter-shell cavity, combined with an impedance gradient design of a graphitized carbon layer, which helps the coating achieve excellent wave absorption capabilities. The dual-cavity structure introduces a large number of air-solid interfaces along the electromagnetic wave propagation path, enhancing interface polarization loss; the highly graphitized inner region of the graphitized carbon layer provides conduction loss, while the low-graphitized outer region facilitates the entry of electromagnetic waves from the air into the coating interior, reducing surface reflection, thereby solving the problems of narrow bandwidth and large matching thickness in single-loss mechanism absorbing materials.
[0032] 2. This invention employs a composite structure of iron(III) oxide and graphitized carbon layers as a photothermal conversion medium, enabling the coating to convert absorbed light energy into heat energy under illumination, thereby raising the surface temperature of the coating. This photothermal effect can melt the thin ice layer on the coating surface or delay ice crystal formation at low temperatures. Combined with the coating's low surface energy and hydrophobic properties, it achieves synergy between passive anti-icing and active de-icing within the same coating system.
[0033] 3. This invention establishes a chemical bond anchoring between the dual-cavity magnetic microwave absorbing filler and the resin matrix through a polysiloxane bridging agent. The phosphate ester groups of this agent anchor the surface of the dual-cavity magnetic microwave absorbing filler, while the epoxy propylene group participates in the curing and crosslinking of the epoxy resin. The active silane-hydrogen bonds undergo a crosslinking reaction with the polysilazane, covalently integrating the filler into the coating's crosslinking network. This solves the problem of weak interfacial bonding and easy debonding in traditional physical blending systems. Simultaneously, the amino functional groups on the surface of the dual-cavity magnetic microwave absorbing filler are key sites for the chemical anchoring of the phosphate ester groups, a crucial prerequisite for achieving this covalently integrated network, ensuring its long-term stability in the coating.
[0034] 4. This invention uses an epoxy-modified polysiloxane resin and an organopolysilazane compound as the film-forming material. Combined with the directional arrangement of perfluorodecyl side groups in the polysiloxane bridging agent on the coating surface, the coating acquires durable low surface energy properties. The perfluorodecyl side groups are chemically bonded to the main chain of the additive and migrate to the surface during curing to form a hydrophobic layer. This chemical bonding method allows the coating to maintain high hydrophobicity even after wear. Simultaneously, the compounded resin system, along with the epoxypropyl groups and active silane-hydrogen bonds on the additive, participates in the crosslinking reaction, enabling the coating to achieve low ice adhesion strength while maintaining good adhesion.
[0035] 5. This invention integrates the microwave absorption and photothermal functions provided by the dual-cavity magnetic microwave absorbing filler, the hydrophobic surface constructed by the polysiloxane bridging agent, and the mechanical properties provided by the organic-inorganic hybrid resin into a single coating system, achieving integrated anti-icing, de-icing, and microwave absorption functions at the material level. The functional components are interconnected through chemical bonds, avoiding interfacial compatibility issues caused by multi-layer coatings or the stacking of multiple functional layers. Attached Figure Description
[0036] Figure 1 This is a cross-sectional schematic diagram of the anti-icing, de-icing, and wave-absorbing multifunctional composite material structure proposed in this invention; where 1 represents the substrate and 2 represents the surface anti-icing coating. Detailed Implementation
[0037] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0038] Example 1: Preparation of Double-Cavity Magnetic Absorbing Filler A1. Add 100.0 g of deionized water, 5.0 g of melamine, and 10.0 g of 37 wt% formaldehyde aqueous solution to a 500 mL three-necked flask equipped with a mechanical stirrer and a reflux condenser. Stir until the melamine is completely dissolved, then adjust the pH to 4.0 with formic acid, heat to 60 °C and react for 2 hours. After centrifugation (6000 rpm, 10 minutes), washing three times alternately with deionized water and anhydrous ethanol, and vacuum drying at 60 °C for 12 hours, melamine-formaldehyde microsphere template is obtained.
[0039] A2. Disperse 5.0 g of the melamine-formaldehyde microsphere template obtained in A1 in a mixed solvent of 100.0 g of anhydrous ethanol and 50.0 g of deionized water. Add 10.0 g of resorcinol, 15.0 g of 37 wt% formaldehyde aqueous solution and 5.0 g of 20 nm nano-iron oxide in sequence. Sonicate the mixture at 40 kHz and 200 W for 30 minutes. Adjust the pH to 9 with ammonia water and react at 60 °C for 4 hours. After centrifugation (6000 rpm, 10 minutes), washing with deionized water and anhydrous ethanol three times alternately, and vacuum drying at 60 °C for 12 hours, core-shell microspheres are obtained.
[0040] A3. Disperse 5.0 g of the core-shell microspheres obtained in A2 in a mixed solution containing 5.0 g of hexadecyltrimethylammonium bromide, 100.0 g of anhydrous ethanol, and 50.0 g of deionized water. Adjust the pH to 9 with ammonia water, heat to 40 °C, add 10.0 g of tetraethyl orthosilicate dropwise over 2 hours, keep the reaction at this temperature for 6 hours, centrifuge (6000 rpm, 10 minutes), wash three times alternately with deionized water and anhydrous ethanol, and vacuum dry at 60 °C for 12 hours to obtain three-layer core-shell microspheres.
[0041] A4. Place the three-layered core-shell microspheres obtained in A3 in a tube furnace, introduce argon gas (flow rate 100 mL / min), raise the temperature to 700℃ at a heating rate of 2℃ / min, hold for carbonization for 2 hours, and allow to cool naturally to room temperature to obtain the carbonized product.
[0042] A5. Disperse 100.0g of the carbonized product obtained in A4 in 200.0g of deionized water, add 5.0g of sodium hydroxide, stir and etch at 60℃ for 2 hours, centrifuge (6000rpm, 10 minutes), wash with deionized water until neutral (pH 7-8), and vacuum dry at 60℃ for 12 hours to obtain a double-cavity core-shell structure packing.
[0043] A6. Disperse 100.0g of the double-cavity core-shell structure packing obtained in A5 in 300.0g of anhydrous ethanol, add 5.0g of deionized water and 2.0g of 3-aminopropyltriethoxysilane, adjust the pH to 8 with ammonia, react at 50℃ for 6 hours, centrifuge (6000rpm, 10 minutes), wash 3 times with anhydrous ethanol, and vacuum dry at 60℃ for 12 hours to obtain the double-cavity magnetic microwave absorbing packing.
[0044] II. Preparation of Polysiloxane Bridging Agents S1. Add 100.0 g of polymethylhydrosiloxane (containing 1.58% hydrogen, i.e., approximately 1.58 mol of active silane-hydrogen bonds per 100 g of polymethylhydrosiloxane, used as the calculation basis) and 100.0 g of toluene to a 250 mL four-necked flask equipped with a mechanical stirrer, reflux condenser, constant pressure dropping funnel, thermometer, and nitrogen inlet. After purging the air three times with nitrogen, maintain the nitrogen pressure and heat to 80 °C. Add 0.05 g of Karstedt catalyst (xylene solution with approximately 2% platinum content). Add 10.0 g of allyl glycidyl ether dropwise over 1 hour. After the addition is complete, maintain the reaction at 80 °C for 4 hours to obtain an epoxy-modified hydrogen-containing polysiloxane solution.
[0045] S2. Cool the S1 reaction system to 70℃, add 0.02g of Karstedt catalyst (xylene solution with a platinum content of about 2%), and add 5.0g of 1H,1H,2H,2H-perfluorodecyl acrylate dropwise over 1 hour. After the addition is complete, keep the reaction at 70℃ for 3 hours to obtain an epoxy / fluoroalkyl co-modified hydrogen-containing polysiloxane solution.
[0046] S3. Cool the S2 reaction system to 55°C, add 0.02 g of Karstedt catalyst (xylene solution with approximately 2% platinum content), and add 2.0 g of dimethyl vinyl phosphate dropwise over 30 minutes, controlling the temperature to not exceed 70°C during the dropwise addition. After the dropwise addition is complete, maintain the reaction at 55°C for 2 hours. After cooling to room temperature, wash the reaction solution twice with 50.0 g of anhydrous ethanol, allow it to stand and separate the layers, separate the lower organic phase, and remove the solvent and low-boiling substances at 80°C and -0.095 MPa vacuum for 1 hour to obtain the polysiloxane bridging agent.
[0047] III. Formulation and Preparation of Anti-icing Coatings Weigh the following components according to the formula: 40.0g of epoxy modified polysiloxane resin (IOTAH-60, Anhui Aiyota Silicon Oil Co., Ltd.), 10.0g of organopolysilazane (IOTA9108, Anhui Aiyota Silicon Oil Co., Ltd.), 5.0g of double-cavity magnetic microwave absorbing filler, 3.0g of polysiloxane bridging agent, 5.0g of curing agent (polyamide Aradur115-3), 0.5g of crosslinking accelerator (triethylenediamine), 1.0g of hydrophobic modifying agent (heptadecyltrimethoxysilane), 0.2g of leveling agent (BYK-306), 0.2g of defoamer (BYK-066N), and 50.0g of mixed solvent (xylene: butyl acetate: propylene glycol methyl ether acetate = 5:2:1).
[0048] Epoxy-modified polysiloxane resin, organopolysilazane, double-cavity magnetic microwave absorbing filler, polysiloxane bridging agent, hydrophobic modifier and mixed solvent are mixed and dispersed at high speed at 1000 rpm for 20 minutes until uniform. Curing agent, crosslinking accelerator, leveling agent and defoamer are added and stirred and mixed evenly to obtain anti-icing coating.
[0049] The anti-icing coating was sprayed onto the surface of a polished, cleaned and dried aluminum alloy substrate. It was first pre-cured at room temperature for 24 hours, and then post-cured at 80°C for 2 hours to obtain a surface anti-icing coating with a thickness of 40μm.
[0050] Example 2: I. Preparation of Double-Cavity Magnetic Absorbing Filler A1. Add 100.0 g of deionized water, 10.0 g of melamine, and 20.0 g of 37 wt% formaldehyde aqueous solution to a 500 mL three-necked flask equipped with a mechanical stirrer and a reflux condenser. Stir until the melamine is completely dissolved, then adjust the pH to 4.8 with formic acid, heat to 70 °C and react for 4 hours. After centrifugation (8000 rpm, 15 minutes), washing three times alternately with deionized water and anhydrous ethanol, and vacuum drying at 70 °C for 18 hours, melamine-formaldehyde microsphere template is obtained.
[0051] A2. 10.0 g of the melamine-formaldehyde microsphere template obtained in A1 was dispersed in a mixed solvent of 100.0 g of anhydrous ethanol and 75.0 g of deionized water. 20.0 g of resorcinol, 30.0 g of 37 wt% formaldehyde aqueous solution and 12.5 g of 35 nm nano-iron oxide were added sequentially. The mixture was ultrasonically dispersed at 60 kHz and 350 W for 45 minutes. The pH was adjusted to 10 with ammonia water and the temperature was raised to 70 °C for 8 hours. After centrifugation (8000 rpm, 15 minutes), washing with deionized water and anhydrous ethanol three times alternately, and vacuum drying at 70 °C for 18 hours, core-shell microspheres were obtained.
[0052] A3. Disperse 12.5 g of the core-shell microspheres obtained in A2 in a mixed solution containing 10.0 g of hexadecyltrimethylammonium bromide, 100.0 g of anhydrous ethanol, and 75.0 g of deionized water. Adjust the pH to 10 with ammonia water, heat to 50 °C, add 20.0 g of tetraethyl orthosilicate dropwise over 3 hours, keep the reaction at this temperature for 9 hours, centrifuge (8000 rpm, 15 minutes), wash three times alternately with deionized water and anhydrous ethanol, and vacuum dry at 70 °C for 18 hours to obtain three-layer core-shell microspheres.
[0053] A4. The three-layered core-shell microspheres obtained in A3 were placed in a tube furnace, and argon gas (flow rate 150 mL / min) was introduced. The temperature was increased to 800℃ at a rate of 3.5℃ / min, and carbonized at this temperature for 4 hours. The carbonized product was then naturally cooled to room temperature.
[0054] A5. Disperse 100.0g of the carbonized product obtained in A4 in 350.0g of deionized water, add 12.5g of sodium hydroxide, stir and etch at 70℃ for 4 hours, centrifuge (8000rpm, 15 minutes), wash with deionized water until neutral (pH 7-8), and vacuum dry at 70℃ for 18 hours to obtain a double-cavity core-shell structure packing.
[0055] A6. Disperse 100.0g of the double-cavity core-shell structure packing obtained in A5 in 400.0g of anhydrous ethanol, add 10.0g of deionized water and 5.0g of 3-aminopropyltriethoxysilane, adjust the pH to 9 with ammonia, react at 60℃ for 9 hours, centrifuge (8000rpm, 15 minutes), wash three times with anhydrous ethanol, and vacuum dry at 70℃ for 18 hours to obtain the double-cavity magnetic microwave absorbing packing.
[0056] II. Preparation of Polysiloxane Bridging Agents S1. Add 100.0 g of polymethylhydrosiloxane (containing 1.58% hydrogen, i.e., approximately 1.58 mol of active silane-hydrogen bonds per 100 g of polymethylhydrosiloxane, used as the calculation basis) and 200.0 g of toluene to a 500 mL four-necked flask equipped with a mechanical stirrer, reflux condenser, constant pressure dropping funnel, thermometer, and nitrogen inlet. After purging the air three times with nitrogen, maintain the nitrogen pressure and heat to 85 °C. Add 0.125 g of Karstedt catalyst (xylene solution with approximately 2% platinum content). Add 15.0 g of allyl glycidyl ether dropwise over 1.5 hours. After the addition is complete, maintain the reaction at 85 °C for 6 hours to obtain an epoxy-modified hydrogen-containing polysiloxane solution.
[0057] S2. Cool the S1 reaction system to 75℃, add 0.06g of Karstedt catalyst (xylene solution with a platinum content of about 2%), and add 10.0g of 1H,1H,2H,2H-perfluorodecyl acrylate dropwise over 1.5 hours. After the addition is complete, keep the reaction at 75℃ for 4.5 hours to obtain an epoxy / fluoroalkyl co-modified hydrogen-containing polysiloxane solution.
[0058] S3. Cool the S2 reaction system to 60°C, add 0.05 g of Karstedt catalyst (xylene solution with approximately 2% platinum content), and add 5.0 g of dimethyl vinyl phosphate dropwise over 45 minutes, controlling the temperature to not exceed 70°C during the dropwise addition. After the dropwise addition is complete, maintain the reaction at 60°C for 3 hours. After cooling to room temperature, wash the reaction solution twice with 80.0 g of anhydrous ethanol, allow it to stand and separate the layers, separate the lower organic phase, and remove the solvent and low-boiling substances at 90°C and a vacuum of -0.096 MPa for 2 hours to obtain the polysiloxane bridging agent.
[0059] III. Formulation and Preparation of Anti-icing Coatings Weigh the following components according to the formula: 55.0g of epoxy modified polysiloxane resin (IOTAH-60, Anhui Aiyota Silicon Oil Co., Ltd.), 20.0g of organopolysilazane (IOTA9108, Anhui Aiyota Silicon Oil Co., Ltd.), 20.0g of double-cavity magnetic microwave absorbing filler, 6.0g of polysiloxane bridging agent, 10.0g of curing agent (polyamide Aradur115-3), 1.75g of crosslinking accelerator (triethylenediamine), 3.0g of hydrophobic modifying agent (heptadecyltrimethoxysilane), 0.6g of leveling agent (BYK-306), 0.6g of defoamer (BYK-066N), and 100.0g of mixed solvent (xylene: butyl acetate: propylene glycol methyl ether acetate = 6:3:2).
[0060] Epoxy-modified polysiloxane resin, organopolysilazane, double-cavity magnetic microwave absorbing filler, polysiloxane bridging agent, hydrophobic modifier and mixed solvent are mixed and dispersed at high speed at 2000 rpm for 30 minutes until uniform. Curing agent, crosslinking accelerator, leveling agent and defoamer are added and stirred and mixed evenly to obtain anti-icing coating.
[0061] The anti-icing coating was sprayed onto the surface of a polished, cleaned and dried aluminum alloy substrate. It was first pre-cured at room temperature for 30 hours, and then post-cured at 90°C for 3 hours to obtain a surface anti-icing coating with a thickness of 60μm.
[0062] Example 3: I. Preparation of Double-Cavity Magnetic Absorbing Filler A1. Add 100.0 g of deionized water, 15.0 g of melamine, and 30.0 g of 37 wt% formaldehyde aqueous solution to a 500 mL three-necked flask equipped with a mechanical stirrer and a reflux condenser. Stir until the melamine is completely dissolved, adjust the pH to 5.5 with formic acid, heat to 80 °C and react for 6 hours. After centrifugation (10000 rpm, 20 minutes), washing three times alternately with deionized water and anhydrous ethanol, and vacuum drying at 80 °C for 24 hours, melamine-formaldehyde microsphere template is obtained.
[0063] A2. 15.0 g of the melamine-formaldehyde microsphere template obtained in A1 was dispersed in a mixed solvent of 100.0 g of anhydrous ethanol and 100.0 g of deionized water. 30.0 g of resorcinol, 45.0 g of 37 wt% formaldehyde aqueous solution and 20.0 g of 50 nm nano-iron oxide were added sequentially. The mixture was ultrasonically dispersed at 80 kHz and 500 W for 60 minutes. The pH was adjusted to 11 with ammonia water, and the mixture was heated to 80 °C and reacted for 12 hours. After centrifugation (10000 rpm, 20 minutes), washing with deionized water and anhydrous ethanol three times alternately, and vacuum drying at 80 °C for 24 hours, core-shell microspheres were obtained.
[0064] A3. Disperse 20.0 g of the core-shell microspheres obtained in A2 in a mixed solution containing 15.0 g of hexadecyltrimethylammonium bromide, 100.0 g of anhydrous ethanol, and 100.0 g of deionized water. Adjust the pH to 11 with ammonia water, raise the temperature to 60°C, add 30.0 g of tetraethyl orthosilicate dropwise over 4 hours, keep the reaction at this temperature for 12 hours, centrifuge (10000 rpm, 20 minutes), wash three times alternately with deionized water and anhydrous ethanol, and vacuum dry at 80°C for 24 hours to obtain three-layer core-shell microspheres.
[0065] A4. Place the three-layered core-shell microspheres obtained in A3 in a tube furnace, introduce argon gas (flow rate 200 mL / min), raise the temperature to 900℃ at a rate of 5℃ / min, hold for carbonization for 6 hours, and allow to cool naturally to room temperature to obtain the carbonized product.
[0066] A5. Disperse 100.0g of the carbonized product obtained in A4 in 500.0g of deionized water, add 20.0g of sodium hydroxide, stir and etch at 80℃ for 6 hours, centrifuge (10000rpm, 20 minutes), wash with deionized water until neutral (pH 7-8), and vacuum dry at 80℃ for 24 hours to obtain a double-cavity core-shell structure packing.
[0067] A6. Disperse 100.0g of the double-cavity core-shell structure packing obtained in A5 in 500.0g of anhydrous ethanol, add 15.0g of deionized water and 8.0g of 3-aminopropyltriethoxysilane, adjust the pH to 10 with ammonia, react at 70℃ for 12 hours, centrifuge (10000rpm, 20min), wash three times with anhydrous ethanol, and vacuum dry at 80℃ for 24 hours to obtain the double-cavity magnetic microwave absorbing packing.
[0068] II. Preparation of Polysiloxane Bridging Agents S1. Add 100.0 g of polymethylhydrosiloxane (containing 1.58% hydrogen, i.e., approximately 1.58 mol of active silane-hydrogen bonds per 100 g of polymethylhydrosiloxane, used as the basis for calculation) and 300.0 g of toluene to a 500 mL four-necked flask equipped with a mechanical stirrer, reflux condenser, constant pressure dropping funnel, thermometer, and nitrogen inlet. After purging the air with nitrogen three times and maintaining positive nitrogen pressure, heat to 90 °C, add 0.20 g of Karstedt catalyst (xylene solution with approximately 2% platinum content), and add 20.0 g of allyl glycidyl ether dropwise over 2 hours. After the addition is complete, maintain the reaction at 90 °C for 8 hours to obtain an epoxy-modified hydrogen-containing polysiloxane solution.
[0069] S2. Cool the S1 reaction system to 80℃, add 0.10g of Karstedt catalyst (xylene solution with a platinum content of about 2%), and add 15.0g of 1H,1H,2H,2H-perfluorodecyl acrylate dropwise over 2 hours. After the addition is complete, keep the reaction at 80℃ for 6 hours to obtain an epoxy / fluoroalkyl co-modified hydrogen-containing polysiloxane solution.
[0070] S3. Cool the S2 reaction system to 65°C, add 0.08 g of Karstedt catalyst (xylene solution with approximately 2% platinum content), and add 8.0 g of dimethyl vinyl phosphate dropwise over 60 minutes, controlling the temperature to not exceed 70°C during the dropwise addition. After the dropwise addition is complete, maintain the reaction at 65°C for 4 hours. After cooling to room temperature, wash the reaction solution twice with 100.0 g of anhydrous ethanol, allow it to stand and separate the layers, separate the lower organic phase, and remove the solvent and low-boiling substances at 100°C and -0.098 MPa vacuum for 3 hours to obtain the polysiloxane bridging agent.
[0071] III. Formulation and Preparation of Anti-icing Coatings Weigh the following components according to the formula: 70.0g of epoxy modified polysiloxane resin (IOTAH-60, Anhui Aiyota Silicon Oil Co., Ltd.), 30.0g of organopolysilazane (IOTA9108, Anhui Aiyota Silicon Oil Co., Ltd.), 25.0g of double-cavity magnetic microwave absorbing filler, 8.0g of polysiloxane bridging agent, 15.0g of curing agent (polyamide Aradur115-3), 3.0g of crosslinking accelerator (triethylenediamine), 5.0g of hydrophobic modifying agent (heptadecyltrimethoxysilane), 1.0g of leveling agent (BYK-306), 1.0g of defoamer (BYK-066N), and 150.0g of mixed solvent (xylene: butyl acetate: propylene glycol methyl ether acetate = 7:4:3).
[0072] Epoxy-modified polysiloxane resin, organopolysilazane, double-cavity magnetic microwave absorbing filler, polysiloxane bridging agent, hydrophobic modifier and mixed solvent are mixed and dispersed at high speed at 3000 rpm for 40 minutes until uniform. Curing agent, crosslinking accelerator, leveling agent and defoamer are added and stirred and mixed evenly to obtain anti-icing coating.
[0073] Anti-icing coating was sprayed onto the surface of a polished, cleaned and dried aluminum alloy substrate. It was first pre-cured at room temperature for 48 hours, and then post-cured at 100℃ for 4 hours to obtain a surface anti-icing coating with a thickness of 80μm.
[0074] Comparative Example 1: Based on Example 2, the difference is that no double-cavity magnetic wave-absorbing filler is added to the anti-icing coating, otherwise it is the same as Example 2.
[0075] Comparative Example 2: Based on Example 2, the difference is that no polysiloxane bridging agent is added to the anti-icing coating, otherwise it is the same as Example 2.
[0076] Comparative Example 3: Based on Example 2, the difference is that an equal amount of ordinary nano-iron oxide (particle size 16-35nm, without carbon layer coating and cavity construction) is used to replace the double-cavity magnetic absorbing filler, and the rest is the same as in Example 2.
[0077] Comparative Example 4: Based on Example 2, the difference is that the surface amino grafting modification in step A6 is omitted in the preparation process of the double-cavity magnetic absorbing filler, and the double-cavity core-shell structure filler obtained in step A5 is used directly. The rest of the operation is the same as in Example 2.
[0078] Performance testing: The above Examples 1-3 and Comparative Examples 1-4 were subjected to the following tests, and the test methods are as follows: 1. Contact angle and roll-off angle: According to GB / T30447-2013, the contact angle was measured using a contact angle measuring instrument. The water droplet volume was 5μL (contact angle) and 10μL (roll-off angle). The average value of 5 positions was taken for each sample.
[0079] 2. Ice adhesion strength: In accordance with ASTM C165-07, ice columns with a diameter of 10 mm and a height of 10 mm (deionized water, frozen for 4 hours) were prepared at -10℃. They were pushed in parallel using a push-pull force gauge (MARK-10 Series 7). The strength was calculated according to τ=F / A. Five ice columns were tested and the average value was taken.
[0080] 3. Freezing delay time: In a -15℃ constant temperature and humidity chamber, 10μL of deionized water was dropped onto the coating surface, and the time from the water droplet contacting the surface to complete freezing was recorded. The average value of 10 water droplets was taken.
[0081] 4. Absorption performance: In accordance with GJB2038A-2011, the reflection loss of the coating (180mm×180mm, backed by an aluminum plate) was tested in the range of 2 to 18 GHz using a vector network analyzer and the bow method. The minimum reflection loss value and the effective absorption bandwidth (<-10dB) were recorded.
[0082] 5. Photothermal heating: A xenon lamp solar simulator vertically irradiates the coating, and an infrared thermal imager records the temperature changes, recording the stable temperature after 5 minutes.
[0083] 6. Adhesion: Tested according to GB / T9286-2021 cross-cut test, with a blade spacing of 2mm and a rating of 0 to 5.
[0084] 7. Abrasion resistance: The water contact angle was measured according to GB / T1768-2006, using a Taber abrasion tester, CS-10 grinding wheel, 500g load, 60rpm, and after 500 revolutions.
[0085] The test results are as follows: Table 1. Test Results of Examples and Comparative Examples Figure 1 This is a cross-sectional schematic diagram of the anti-icing, de-icing, and wave-absorbing multifunctional composite material structure proposed in this invention; where 1 represents the substrate and 2 represents the surface anti-icing coating.
[0086] Data Analysis: Analysis of Table 1 shows that the coatings prepared in Examples 1-3 all have a water contact angle greater than or equal to 152°, a roll-off angle not exceeding 6°, an ice adhesion strength not exceeding 25 kPa, an ice-freezing delay time not less than 380 s, a minimum reflection loss not exceeding -28 dB, an effective absorption bandwidth not less than 3.8 GHz, an adhesion grade of 0-1, a water contact angle after wear resistance not less than 148°, and a light-stable temperature not less than 78℃. Regarding wear resistance, after 500 rpm wear resistance tests, the water contact angle of Examples 1-3 only decreased by 4-8°, remaining at a superhydrophobic level above 150°. This is mainly attributed to two aspects: the structural stability of the interfacial chemical bonding: the polysiloxane bridging agent anchors the filler through phosphate ester groups and crosslinks with the resin network through epoxy groups and active silane-hydrogen bonds, constructing a strong and tough filler-resin interface. During wear, this chemically bonded network effectively prevents the shedding of filler particles, maintaining the micro-nano roughness of the coating surface and avoiding a sharp drop in hydrophobicity due to structural damage.
[0087] The persistent presence of low surface energy components: The perfluorodecyl side chains in the polysiloxane bridging agent are chemically bonded to the resin molecular chains, rather than through simple physical adsorption. Even after minor wear of the surface material, the newly exposed surface still contains chemically bonded low surface energy fluorocarbon segments, thus enabling the coating to maintain a low surface energy even after wear.
[0088] Comparative Example 1 did not include the dual-cavity magnetic absorbing filler. Compared to Example 2, the ice adhesion strength increased from 18 kPa to 65 kPa, the freezing delay time decreased from 450 s to 120 s, the minimum reflection loss decreased from -38.2 dB to -5.2 dB, and the photothermal stability temperature decreased from 86 °C to 52 °C. Its contact angle of 150° and roll-off angle of 8° still met the superhydrophobicity criterion, indicating that the perfluorodecyl side groups of the fluorosilane and polysiloxane bridging aids in the resin matrix can still form a low surface energy layer. However, the deterioration in ice adhesion strength and freezing delay time indicates that the micro-nano rough structure provided by the dual-cavity magnetic absorbing filler is key to reducing the mechanical locking of ice crystals. This dual-cavity magnetic absorbing filler is also the basis for the coating to achieve electromagnetic loss and photothermal conversion.
[0089] Comparative Example 2 did not include a polysiloxane bridging agent. Compared to Example 2, the water contact angle decreased from 158° to 142°, the roll-off angle increased from 4° to 15°, and the superhydrophobicity criterion was no longer met. After wear resistance, the contact angle decreased from 153° to 128°, the adhesion grade decreased from 0 to 3, and the ice adhesion strength increased from 18 kPa to 45 kPa. Without the polysiloxane bridging agent, the perfluorodecyl side groups could not effectively migrate to the surface, resulting in a degradation of hydrophobic properties. The lack of co-curing of epoxy side groups with epoxy resin and cross-linking of active silane bonds with polysilazane prevented the formation of chemical bonds between the double-cavity magnetic microwave absorbing filler and the resin, significantly reducing wear resistance and adhesion.
[0090] Comparative Example 3 used ordinary nano-ferric oxide (Fe3O4) instead of the double-cavity magnetic absorbing filler. Compared with Example 2, the water contact angle decreased from 158° to 148°, the ice adhesion strength increased from 18 kPa to 52 kPa, the freezing delay time decreased from 450 s to 260 s, the minimum reflection loss decreased from -38.2 dB to -18.4 dB, the effective absorption bandwidth decreased from 5.2 GHz to 2.1 GHz, and the photothermal stability temperature decreased from 86 °C to 58 °C. The absorption and photothermal capabilities of ordinary Fe3O4 are far inferior to those of the double-cavity magnetic absorbing filler. This is because the double-cavity structure introduces a large number of air-solid interfaces in the electromagnetic wave propagation path, which can generate interfacial polarization losses; the high degree of graphitization in the inner layer of the graphitized carbon layer provides conduction loss, while the low degree of graphitization in the outer layer is beneficial for impedance matching. The synergistic effect of the broad-spectrum absorption of the carbon layer coating structure and Fe3O4 is the basis for efficient photothermal conversion.
[0091] Compared to Example 2, Comparative Example 4 showed a decrease in water contact angle from 158° to 134°, an increase in roll-off angle from 4° to 22°, failing to meet the basic criteria for superhydrophobic coatings; adhesion grade decreased from 0 to 4; after wear resistance, the water contact angle decreased from 153° to 110°; ice adhesion strength increased from 18 kPa to 58 kPa, and freezing delay time decreased from 450 s to 180 s. However, the minimum reflection loss (-36.5 dB), effective absorption bandwidth (4.8 GHz), and photothermal stability temperature (84 °C) remained essentially the same as in Example 2. These results indicate that the amino functional groups on the filler surface are key sites for the chemical anchoring of the polysiloxane bridging agent's phosphate ester groups. Without amino surface modification, the additive cannot establish stable chemical bonds with the filler, resulting in the ineffective construction of the integrated "filler-additive-resin" network, and significant deterioration in the coating's hydrophobicity, adhesion, wear resistance, and anti-icing performance. The microwave absorption and photothermal functions mainly rely on the structure of the double-cavity filler itself, which is relatively decoupled from the chemical bonding network, so these two properties are less affected.
[0092] The results of Comparative Example 4 and Comparative Example 2 (completely without additives) corroborate each other: even if additive molecules are present, if they cannot form chemical bonds with the filler (Comparative Example 4), their performance is still far lower than that of the chemically bonded state (Example 2), indicating that the "amino grafting-phosphate anchoring" chemical bonding design in this invention is an indispensable key feature for achieving multifunctional synergy.
[0093] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A multifunctional composite material structure for anti-icing, de-icing, and wave absorption, comprising a substrate and a surface anti-icing coating disposed on the surface of the substrate, characterized in that, The surface anti-icing coating is formed by curing an anti-icing paint, which contains the following components: epoxy-modified polysiloxane resin, organopolysilazane, double-cavity magnetic microwave absorbing filler, polysiloxane bridging agent, curing agent, crosslinking accelerator, hydrophobic modification agent, leveling agent, defoamer, and mixed solvent. The dual-cavity magnetic absorbing filler is a multi-layer core-shell structure formed by template pyrolysis to create an inner cavity and selective etching between the carbon layer and the mesoporous silica shell to create an inter-shell cavity. The carbon layer contains iron oxide nanoparticles, and the surface of the mesoporous silica shell is grafted with amino functional groups. The polysiloxane bridging agent has a polymethylhydrosiloxane backbone, on which three side groups—epoxypropyl, perfluorodecyl, and phosphate ester—are grafted, and active silane-hydrogen bonds are retained.
2. The anti-icing, de-icing, and wave-absorbing multifunctional composite material structure according to claim 1, characterized in that, By weight, the anti-icing coating comprises 40-70 parts of epoxy-modified polysiloxane resin, 10-30 parts of organopolysilazane, 5-25 parts of double-cavity magnetic microwave absorbing filler, 3-8 parts of polysiloxane bridging agent, 5-15 parts of curing agent, 0.5-3 parts of crosslinking accelerator, 1-5 parts of hydrophobic modifying agent, 0.2-1.0 parts of leveling agent, 0.2-1.0 parts of defoamer, and 50-150 parts of mixed solvent.
3. The anti-icing, de-icing, and wave-absorbing multifunctional composite material structure according to claim 1, characterized in that, The dual-cavity magnetic absorbing filler is prepared by a method comprising the following steps: A1. Add deionized water, melamine, and 37wt% formaldehyde aqueous solution to a reaction vessel, stir to dissolve, adjust the pH to 4.0-5.5 with formic acid, heat to 60-80℃ and react for 2-6 hours, centrifuge, wash and dry to obtain melamine-formaldehyde microsphere template, wherein the weight ratio of melamine, 37wt% formaldehyde aqueous solution and deionized water is 5-15:10-30:100; A2. The melamine-formaldehyde microsphere template obtained in A1 was dispersed in a mixed solvent of anhydrous ethanol and deionized water. Resorcinol, 37wt% formaldehyde aqueous solution, and nano-iron oxide with a particle size of 20-50nm were added sequentially. After ultrasonic dispersion, the pH was adjusted to 9-11 with ammonia water, and the temperature was raised to 60-80℃ for 4-12 hours. After centrifugation, washing, and drying, core-shell microspheres were obtained. The weight ratio of melamine-formaldehyde microsphere template, resorcinol, 37wt% formaldehyde aqueous solution, nano-iron oxide, anhydrous ethanol, and deionized water was 5-15:10-30:15-45:5-20:100:50-100. A3. The core-shell microspheres obtained in A2 were dispersed in a mixed solution of anhydrous ethanol and deionized water containing hexadecyltrimethylammonium bromide. The pH was adjusted to 9-11 with ammonia. The temperature was raised to 40-60℃ and tetraethyl orthosilicate was added dropwise. The reaction was maintained at this temperature for 6-12 hours. After centrifugation, washing and drying, three-layer core-shell microspheres were obtained. The weight ratio of core-shell microspheres, tetraethyl orthosilicate, hexadecyltrimethylammonium bromide, anhydrous ethanol and deionized water was 5-20:10-30:5-15:100:50-100. A4. The three-layered core-shell microspheres obtained in A3 were placed in a tube furnace and heated to 700-900℃ under argon protection at a rate of 2-5℃ / min and held for carbonization for 2-6 hours. The carbonized products were then obtained by natural cooling. A5. Disperse the carbonized product obtained in A4 in deionized water, add sodium hydroxide and stir and etch at 60-80℃ for 2-6 hours, and obtain a double-cavity core-shell structure packing material by centrifugation, washing and drying, wherein the weight ratio of carbonized product, sodium hydroxide and deionized water is 100:5-20:200-500. A6. The double-cavity core-shell structure packing obtained in A5 is dispersed in anhydrous ethanol, deionized water and 3-aminopropyltriethoxysilane are added, the pH is adjusted to 8-10 with ammonia, and the reaction is carried out at 50-70℃ for 6-12 hours. After centrifugation, washing and drying, the double-cavity magnetic absorbing packing is obtained, wherein the weight ratio of the double-cavity core-shell structure packing, 3-aminopropyltriethoxysilane, anhydrous ethanol and deionized water is 100:2-8:300-500:5-15.
4. The anti-icing, de-icing, and wave-absorbing multifunctional composite material structure according to claim 1, characterized in that, The polysiloxane bridging agent is prepared by a method comprising the following steps: S1. Add polymethylhydrosiloxane and toluene to a reaction vessel equipped with a stirrer and a nitrogen purging device, purge with nitrogen and heat to 80-90°C, add Karstedt catalyst, the amount of Karstedt catalyst being 0.05%-0.2% of the mass of polymethylhydrosiloxane, add allyl glycidyl ether dropwise, the amount of allyl glycidyl ether being 4%-12% of the total molar number of active silane-hydrogen bonds in the polymethylhydrosiloxane, the dropwise addition time being 1-2 hours, and keep the reaction at the temperature for 4-8 hours to obtain an epoxy-modified hydrogen-containing polysiloxane solution; S2. Cool the S1 epoxy-modified hydrogen-containing polysiloxane solution to 70-80°C, add Karstedt catalyst, the amount of Karstedt catalyst added is 0.02%-0.1% of the mass of the polymethylhydrosiloxane, add 1H,1H,2H,2H-perfluorodecyl acrylate dropwise, the amount of 1H,1H,2H,2H-perfluorodecyl acrylate is calculated as 0.5%-3.0% of the total molar number of initial active silane-hydrogen bonds in the polymethylhydrosiloxane, the dropwise addition time is 1-2 hours, and the reaction is kept at the temperature for 3-6 hours to obtain an epoxy / fluoroalkyl co-modified hydrogen-containing polysiloxane solution; S3. Cool the S2 epoxy / fluoroalkyl co-modified hydrogen-containing polysiloxane solution to 55-65°C, add Karstedt catalyst (0.02%-0.08% of the mass of the polymethylhydrosiloxane), and add vinyl dimethyl phosphate (0.5%-5.0% of the total molar number of initial active Silane-hydrogen bonds in the polymethylhydrosiloxane). Control the temperature during the addition process to not exceed 70°C, and the addition time to be 30-60 minutes. Maintain the reaction temperature for 2-4 hours. After washing with ethanol, allow the mixture to stand and separate into layers, separate the lower organic phase, and remove the solvent under vacuum to obtain the polysiloxane bridging agent.
5. The anti-icing, de-icing, and wave-absorbing multifunctional composite material structure according to claim 3, characterized in that, The melamine-formaldehyde microsphere template described in A1 has a particle size of 0.5–5.0 μm.
6. The anti-icing, de-icing, and wave-absorbing multifunctional composite material structure according to claim 3, characterized in that, The sodium hydroxide etching temperature described in A5 is 60–80°C, and the etching time is 2–6 hours.
7. The anti-icing, de-icing, and wave-absorbing multifunctional composite material structure according to claim 4, characterized in that, The polymethylhydrosiloxane described in S1 has a hydrogen content ≥1.58% and a viscosity of 15–40 mm at 25°C. 2 / s; the amount of toluene used is 1 to 3 times the mass of polymethylhydrosiloxane.
8. The anti-icing, de-icing, and wave-absorbing multifunctional composite material structure according to claim 4, characterized in that, The temperature for vacuum solvent removal described in S3 is 80–100°C, and the vacuum degree is -0.095–-0.098 MPa.
9. The anti-icing, de-icing, and wave-absorbing multifunctional composite material structure according to claim 1, characterized in that, The curing agent is an amine curing agent or an anhydride curing agent, the crosslinking accelerator is triethylenediamine, the hydrophobic modifying agent is heptadecafluorodecyltrimethoxysilane, the leveling agent is polyether-modified polysiloxane, the defoamer is a polysiloxane defoamer, the mixed solvent is a mixture of xylene, butyl acetate and propylene glycol methyl ether acetate, with a weight ratio of 5-7:2-4:1-3, and the thickness of the surface anti-icing coating is 40-80 μm.
10. A method for preparing a multifunctional composite material structure for anti-icing and wave absorption as described in claim 1, characterized in that, Includes the following steps: The first step is substrate surface treatment: the substrate surface is sanded, cleaned and dried; The second step is coating preparation: epoxy modified polysiloxane resin, organopolysilazane, double-cavity magnetic microwave absorbing filler, polysiloxane bridging agent, hydrophobic modification agent and mixed solvent are mixed and dispersed at high speed at 1000-3000 rpm for 20-40 minutes until uniform. Then, curing agent, crosslinking accelerator, leveling agent and defoamer are added and stirred and mixed evenly to obtain anti-icing coating. The third step is coating and curing: the anti-icing coating is applied to the surface of the treated substrate, pre-cured at room temperature for 24 to 48 hours, and then post-cured by heating at 80 to 100°C for 2 to 4 hours to obtain the surface anti-icing coating.